Currarino Syndrome (SC): A case at the University Hospital of Mother and Child Lagune Cotonou - GBENOU, ANTOINE SÉRAPHIN; Akodjenou, Joseph; SEÏDOU, FALILATOU; ADEOTI, F.; FIOGBE, ARMAND MICHEL; Akele Akpo, Marie T.; BANKOLE, R. (My University, 2021)
Introduction: The Currarino syndrome (CS) is one of the rare syndromic forms of anorectal malformations (ARM). Observation: This is the clinical case of a 3 days male newborn admitted for high ARM in the pediatric surgery Department of the Lagune Mother and Child University Hospital of Cotonou. An emergency colostomy was performed. At the age of 7 months as a prelude to anorectoplasty, the distal colography revealed a semilunar pelvic opacity in front of the sacrum. The posterior sagittal approach according to Peña could not reveal the distal end of the intestine. The reconstruction of the sphincter-muscular complex was done on a tracheal tube. The abdominal approach allowed the discovery and resection of a presacral mass. The rectal pouch end found was then lowered. Post-operative follows up was uneventful. The standard postoperative X-ray revealed a partial agenesis of the sacrum. The histology of the operative specimen found a cystic lipoma. The diagnosis of CS was done. The search of a HLXB9 mutation was not possible. Conclusion: The clinical observation associated with standard radiological investigations highlighted the triad: anorectal malformation, presacral tumor, and partial agenesis of the sacrum, which upheld the diagnosis of CS; but the search for an indispensable HLXB9 mutation was lacking for the genetic link.
Keywords: anorectal malformation; currarino syndrome; child